1993
DOI: 10.1111/j.1524-4725.1993.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocyst of the Auricle

Abstract: Pseudocyst of the auricle can be successfully managed by surgical excision of the anterior wall of the cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
(39 reference statements)
1
14
1
Order By: Relevance
“…Further support for this hypothesis comes from reports of PCA occurring secondary to repeated rubbing of the ears in patients with generalized intense pruritic conditions such as AD or lymphoma 2,4 . In fact, association of PCA with malignancy has only been reported previously in two men, who both had lymphoma with secondary generalized itching 4,5 . To our knowledge, the current patient is only the third reported case of PCA associated with malignancy and the first with an associated HCC.…”
supporting
confidence: 57%
“…Further support for this hypothesis comes from reports of PCA occurring secondary to repeated rubbing of the ears in patients with generalized intense pruritic conditions such as AD or lymphoma 2,4 . In fact, association of PCA with malignancy has only been reported previously in two men, who both had lymphoma with secondary generalized itching 4,5 . To our knowledge, the current patient is only the third reported case of PCA associated with malignancy and the first with an associated HCC.…”
supporting
confidence: 57%
“…Chang et al [26] and Kanotra [9] found no recurrence after removing anterior leaflet of the pseudocyst. Hoffman et al [27] and Mohammed et al [28] successfully treated patients with this technique. Though this procedure is the best, it is associated with minor complications as seen in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Hoffman et al . [22] and Mohammed and Jakubikova[23] successfully treated patients with this technique. A previous study in our department by Patigaroo et al .…”
Section: Discussionmentioning
confidence: 99%